Etika dan Peran Notaris Dalam Mengeluarkan Akta Waris (Contoh Kasus Notaris A Pada Tahun 2018) - Albeth Albeth; Gunawan Djajaputra (Fakultas Hukum Universitas Tarumanagara, 2019)
Ethics is a collection of principles or values relating to norms that live in society that are generally recognized as a moral method as guidelines in behavior. in carrying out their duties, the notary must rely on professional ethics that have been recorded or regulations that have been written and are binding and must be obeyed by all members of the professional group to be obeyed and may be subject to sanctions for those who violate these provisions. In notarial practice in Indonesia, many notary people violate the ethics of the notary profession itself, the last few years many violations committed by notaries, this can be seen from several problems regarding the making of the deed. then the notary is responsible for the changes made by him, responsibility is a result of the consequences of a person's freedom of conduct related to ethics or morals in carrying out an act. how the responsibility of a Notary Public in Making a Deed of Inheritance (Example of a notary case A in 2018) is a matter that is discussed. Descriptive research methods, using secondary data and primary data as supporting data, were analyzed qualitatively. The results of the study illustrate that the Notary does not follow the professional ethics of a notary that has been regulated by the Indonesian Notary Association (INI).